2021
DOI: 10.1214/21-ejs1807
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic projection of the von Mises–Fisher distribution for projection pursuit of directional data

Abstract: We investigate geodesic projections of von Mises-Fisher (vMF) distributed directional data. The vMF distribution for random directions on the (p − 1)-dimensional unit hypersphere S p−1 ⊂ R p plays the role of multivariate normal distribution in directional statistics. For one-dimensional circle S 1 , the vMF distribution is called von Mises (vM) distribution. Projections onto geodesics are one of main ingredients of modeling and exploring directional data. We show that the projection of vMF distributed random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The distribution of hitting points, X T , on the response sphere is given by the von Mises–Fisher distribution (Gatto, 2013; Hillen et al, 2017), which has probability density functionwhere (boldμfalse¯·trueX¯bold-italicT) is the dot product of the unit vectors boldμfalse¯ = μ/ ‖ μ ‖ and trueX¯T=XT/a and κ is again given by Equation 3. Jung (2021) showed that the marginal distribution of a von Mises–Fisher distribution projected onto a geodesic (a great circle) of the sphere is not a von Mises distribution but is sufficiently close to be indistinguishable from it numerically. So, while the marginal distributions of the spherical diffusion model are not exactly von Mises in form—unlike the circular diffusion model—they approximate it sufficiently well to be plausible alternative models for the distribution of errors in continuous-outcome tasks.…”
Section: A Spherical Generalization Of the Circular Diffusion Modelmentioning
confidence: 99%
“…The distribution of hitting points, X T , on the response sphere is given by the von Mises–Fisher distribution (Gatto, 2013; Hillen et al, 2017), which has probability density functionwhere (boldμfalse¯·trueX¯bold-italicT) is the dot product of the unit vectors boldμfalse¯ = μ/ ‖ μ ‖ and trueX¯T=XT/a and κ is again given by Equation 3. Jung (2021) showed that the marginal distribution of a von Mises–Fisher distribution projected onto a geodesic (a great circle) of the sphere is not a von Mises distribution but is sufficiently close to be indistinguishable from it numerically. So, while the marginal distributions of the spherical diffusion model are not exactly von Mises in form—unlike the circular diffusion model—they approximate it sufficiently well to be plausible alternative models for the distribution of errors in continuous-outcome tasks.…”
Section: A Spherical Generalization Of the Circular Diffusion Modelmentioning
confidence: 99%
“…In the particular case in which we want to compute SSW 2 between a measure µ and the uniform measure on the sphere ν = Unif(S d−1 ), we can use the appealing fact that the projection of ν on the circle is uniform, i.e. P U # ν = Unif(S 1 ) (particular case of Theorem 3.1 in [55], see Appendix B.3). Hence, we can use the Proposition 1 to compute W 2 , which allows a very efficient implementation either by the closed-form (13) or approximation by rectangle method of ( 12).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, to define a sliced-Wasserstein discrepancy on this manifold, we propose, analogously to the classical SW distance, to project measures on great circles. The most natural way to project points from S d−1 to a great circle C is to use the geodesic projection [40,55] defined as…”
Section: Definition Of Sw On the Spherementioning
confidence: 99%
See 1 more Smart Citation
“…where μ • XT is the dot product of the unit vectors μ = µ/ µ and XT = X T /a and κ is again given by Equation 3. Jung (2021) showed that the marginal distribution of a von…”
Section: A Spherical Generalization Of the Circular Diffusion Modelmentioning
confidence: 99%